2014
DOI: 10.1039/c3sc53299b
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an orthogonal ZnSalen/Salophen library as a colour palette for one- and two-photon live cell imaging

Abstract: Construction of a colour palette based on modular "core" dyes with tuneable emission and tailor-made intracellular localization is of importance to visualize and distinguish different organelles and even observe their intracellular cross-talking. However, due to lack of structural information linking photophysical properties and the specificity of subcellular localizations, the modification of photophysical properties cannot always enable tailor-made specificity. In this work, we report the construction of a Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 61 publications
3
57
1
1
Order By: Relevance
“…The two main absorption bands at near 300 and 400 nm can be assigned to salophen-centered π-π* transitions. Different from the previously reported Zn salen complexes [17,21,31], no intramolecular charge-transfer transition bands between 500-600 nm is observed for there is no "D-π-A" structure in the salophen ligands. The absorption peaks of LAl 3 red-shifts ca.…”
Section: Uv-vis and Fluorescent Spectracontrasting
confidence: 44%
See 1 more Smart Citation
“…The two main absorption bands at near 300 and 400 nm can be assigned to salophen-centered π-π* transitions. Different from the previously reported Zn salen complexes [17,21,31], no intramolecular charge-transfer transition bands between 500-600 nm is observed for there is no "D-π-A" structure in the salophen ligands. The absorption peaks of LAl 3 red-shifts ca.…”
Section: Uv-vis and Fluorescent Spectracontrasting
confidence: 44%
“…In our group, a series of Zn salen/salophen complexes have been reported as fluorescent probes for cell imaging even with super-resolution, with multiple functions such as intracellular reactive oxygen species, monitoring the lipid droplets and autophagy processes [17][18][19][20][21][22][23]. However, Zn salen complexes tend to aggregate through the axial intermolecular interactions between the Zn center and the phenolic oxygen of another molecule, especially in non-coordinating solvents [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…32) as a color palette for one-and two-photon live cell imaging [235]. The d 10 metal Zn(II) is a bioavailable metal widely found in metalloenzymes [236].…”
Section: Other Cell Organellesmentioning
confidence: 99%
“…Through the construction of a fluorescent Zn(salen) library of 48 complexes, the relationship between the molecular structures, the photophysical properties, and the subcellular distribution of Zn(salen)s were carefully studied . Experimental and theoretical results demonstrated that changes in the diamine moieties could effectively modulate the photophysical properties of the Zn(salen)s. The subcellular localizations were strongly related to the lipophilicity, which is correlated to the N‐substituents at the 4‐position of the salicylaldehyde motifs (Figure ).…”
Section: Metallosalens For Fluorescence Molecular Imagingmentioning
confidence: 99%